Lip reading for Malayalam Text Entry - Jahfar C (International Journal of Interdisciplinary and Multidisciplinary Studies (IJIMS), 2015)
Voice recognition systems [2][5] are used for text entry in many situations. But they are not useful in highly noisy environments or even in areas where the sound is not a preferable option. Also it is not useful for physically challenged people like deaf and dump. Facial gesture interfaces [3][4] can be used for text entry in these environments and also for those people. Facial gesture interfaces, which respond to deliberate facial actions, have received comparatively little attention and also they are in its new born stage. Still researches are going on in these subjects and a comparatively good sign of success is obtained in Japanese language. In this paper we propose an interface which uses a coordinated action of hand and mouth [1], for a user to do Malayalam text entry